Influence of Spirituality on Teaching (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Etymologically, the term spirituality is derived from the word Spirit which comes from the Latin spiritus, meaning breath. This suggests something elusive and yet vital. Spirituality is the wholeness of being connected to something greater than you. This is a very abstract definition of spirituality. It is very difficult to try and engage the meaning of spirituality without being abstract. Some may think that spirituality is a synonym for faith and thus, it is a religious term. This is not necessarily true. Spirituality can be and should be a large part of religious experience. Spirituality can also refer to ones self exploration in the form of meditation, prayer and contemplation. These practices allow a person to be in tune with the essence of their being. Spirituality could also be a way of looking out into nature and feeling a connection.